Solidaritas Mendorong Keadilan Transformatif: Menjemput Pemulihan Bagi Korban Kekerasan Seksual - Iqraa Runi Aprilia (Jurnal Perempuan, 2021)
The slow ratification of the elimination of sexual violence draft law is evidence that the political system in Indonesia insensitive in responding to the issue of sexual violence victims. Meanwhile, the existing justice system has not been able to provide justice for sexual violence victims. That is why feminists formulate a justice that can meet the needs of sexual violence victims, which is called transformative justice. Transformative justice supported by community solidarity can bring about recovery for sexual violence victims to have courage to speak up and regain their destroyed self-esteem.